Establishing Content Validity of the Scale for Evaluating Professional Development Programme Design in Secondary Education - Zou, Yajie; Ahmad, Jamil Bin; Alias, Bity Salwana (Journal of Posthumanism, 2026)
Existing professional development instruments are widely used to evaluate programme quality, yet many rely on broad satisfaction indicators and lack sensitivity to the organisational realities of secondary education. This study establishes the content validity of the Scale for Evaluating Professional Development Programme Design, adapted from Desimone’s five-feature framework. A panel of six experts from academic, administrative, policy, and school-based backgrounds reviewed 28 items across five dimensions—Content Focus, Active Learning, Coherence, Duration, and Collective Participation—using a four-point relevance scale. Item-Level Content Validity Index (I-CVI) values met accepted thresholds (≥0.83), and scale-level indices (S-CVI/Ave) ranged from 0.93 to 1.00. Quantitative results were complemented by qualitative feedback, leading to refinement of four items to improve clarity and alignment with secondary-school organisational structures. Overall, the findings support the SEPDD as a content-valid instrument for evaluating PD programme design in secondary education and informing evidence-based administrative decision-making.